2010
DOI: 10.2478/s11536-009-0089-3
|View full text |Cite
|
Sign up to set email alerts
|

Differences in clinical predictors of influenza in adults and children with influenza-like illness

Abstract: AbstractInfluenza contributes significantly to morbidity and mortality in the winter season. The aim of the study was to identify clinical signs and symptoms most predictive of influenza infection in children and adults with influenza-like illness. A prospective systematic sampling analysis of clinical data collected through sentinel surveillance system for influenza in 32 primary care centers and one tertiary care hospital in Slovenia during two consecutive influenza seasons (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 26 publications
0
21
0
Order By: Relevance
“…Influenza is associated with a variety of signs and symptoms that may vary by age, underlying chronic disease, complications, host immune status, and influenza virus type or influenza A virus subtype. Abrupt onset of fever with cough is most predictive of uncomplicated influenza in adult outpatients, with a sensitivity of >70% during the influenza season [2629]. A retrospective, cross-sectional study in a single urban US emergency department found that the best predictive model for identifying influenza for all ages consisted of cough (diagnostic odds ratio [DOR], 5.87), fever (DOR, 4.49), rhinorrhea (DOR, 1.98), and myalgias (DOR, 1.44) [30].…”
Section: Introductionmentioning
confidence: 99%
“…Influenza is associated with a variety of signs and symptoms that may vary by age, underlying chronic disease, complications, host immune status, and influenza virus type or influenza A virus subtype. Abrupt onset of fever with cough is most predictive of uncomplicated influenza in adult outpatients, with a sensitivity of >70% during the influenza season [2629]. A retrospective, cross-sectional study in a single urban US emergency department found that the best predictive model for identifying influenza for all ages consisted of cough (diagnostic odds ratio [DOR], 5.87), fever (DOR, 4.49), rhinorrhea (DOR, 1.98), and myalgias (DOR, 1.44) [30].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies reporting on symptoms associated with influenza showed cough and fever as the best predictors for influenza infection in adults [11][12][13][14], or muscle/joint pain and nasal congestion to be associated with influenza in all age groups [15]. In children, fever, headache, cough and absence of abnormal breathing sounds [14] or cough, headache and pharyngitis [16] or myalgia (among 1-5-year-olds) [17] were reported to be associated with influenza.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies reporting on symptoms associated with influenza showed cough and fever as the best predictors for influenza infection in adults [11][12][13][14], or muscle/joint pain and nasal congestion to be associated with influenza in all age groups [15]. In children, fever, headache, cough and absence of abnormal breathing sounds [14] or cough, headache and pharyngitis [16] or myalgia (among 1-5-year-olds) [17] were reported to be associated with influenza. Recent reports on the clinical features associated with A(H1N1) 2009 influenza in children showed that headache and myalgia were positively associated [18] or fever, rhinorrhoea, a normal chest radiograph and the absence of leukocytosis or significant gastrointestinal symptoms were positively associated [19].…”
Section: Discussionmentioning
confidence: 97%
“…In children 5-12 years of age, fever ≥38.2°C, cough, and headache were found to be predictive of influenza, whereas in children 1-4 years of age, the only symptom that increased the likelihood of influenza was myalgia. Recently, Sočan et al reported on the clinical predictors of influenza in primary care and tertiary hospital clinic patients who were selected for influenza testing by several predetermined clinical criteria [18]. Fever ≥38°C, headache, cough, and lack of abnormal breathing sounds were found to be predictive of influenza in children less than 15 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…Besides optimizing the use of antiviral drugs, increased accuracy of identifying influenza virus infections would help avoid the unnecessary use of antibiotics and laboratory tests in children [15] and also improve the proper cohorting of patients on wards. Although some previous studies have assessed the predictive value of signs and symptoms for influenza in selected groups of children [16][17][18], few data are available on unselected outpatient children who form the majority of pediatric patients seeking medical care during any influenza outbreak [8,19]. Further, age is an important confounding factor because the clinical features of influenza in children vary with age [20].…”
Section: Introductionmentioning
confidence: 99%